Enhancing Soybean Yield Through Inoculation of Multifunctional Microbial Consortia - Travençoli Rossetim, Murilo Francisco; Vargas Motta, Antonio Carlos; Rocha Kondo, Yanka; Santos Ruthes, Barbara Elis; Hungria, Mariangela; Falcão Salles, Joana; Kaschuk, Glaciela (International journal of agronomy, 2025)
Inoculating multifunctional microbial consortia offers potential benefits for enhancing plant growth and grain yield formation. This study verified the feasibility of inoculating soybean ( Glycine max ) seeds with multifunctional microbial consortia to improve soybean productivity. Seeds were inoculated with 12 combinations of inoculants [ Bradyrhizobium japonicum and B . diazoefficiens for biological N 2 fixation, Azospirillum brasilense for growth promotion via phytohormone release, Bacillus megaterium (= Priestia megaterium ) and B. subtilis for enhancing P uptake, and Trichoderma harzianum as biopesticide] and grown in BOD chamber, greenhouse, and field experiments. In the chamber, inoculated seeds were subjected to germination tests. In the greenhouse, inoculated seeds were sown in pots with nonsterile soil, and plant growth was monitored until the flowering stage. In the field, plants were cultivated until physiological maturity. Soil and plant samples were collected at three growth stages: vegetative, reproductive, and maturation. Measurements included shoot, root, nodules, grain masses, and grain yield, alongside analyses of seed N, P, lipid, protein, and carbohydrate contents. The highest number of microbial inputs and the inclusion of T. harzianum in the microbial consortia impeded seed germination, hindered initial vegetative growth, and decreased plant densities in the plots. Likely due to the crop’s plasticity and the stimulation of microorganisms, the initial setbacks did not affect grain yield and soybean grain lipid content. Therefore, inoculating multifunctional microbial consortia holds promise as a sustainable approach in agriculture. Still, care should be taken concerning an excessive number of inoculants composing the consortia.